More schooling is associated with lower hemoglobin A1c at the high-risk tail of the distribution: an unconditional quantile regression analysis - Jillian Hebert; Amanda M. Irish; Aayush Khadka; Abigail Arons; Alicia R. Riley; Elbert S. Huang; Anusha M. Vable (BMC Public Health)
Abstract Background Risk of diabetes increases exponentially with higher levels of glycosylated hemoglobin (HbA1c). Education is inversely associated with average HbA1c, however, differential associations between education and HbA1c across the HbA1c distribution have not been evaluated. Methods Health and Retirement Study data (N = 21,732) was used to evaluate the association between education (linear terms among those with < 12 years and ≥ 12 years of education) and first recorded HbA1c (2003–2016) at the mean using linear regression, and at the 1st-99th quantiles of the marginal outcome distribution using unconditional quantile regressions, controlling for birth year, race and ethnicity, gender, birthplace, parental education, and year of HbA1c measurement. Results Mean HbA1c was 5.9%; 16.6% of participants had HbA1c above the diabetes diagnostic threshold of 6.5%. For those with fewer than 12 years of schooling, there was no association between education and HbA1c at the mean or across the quantiles. For those with 12 or more years of schooling, an additional year of education was negatively associated with mean HbA1c (βOLS=-0.02, 95% confidence interval (CI) -0.03,-0.02); a one-year increase in mean education was associated with lower HbA1c across the distribution, but the magnitude was larger at higher quantiles (βq50=-0.02, 95%CI -0.02,-0.01; βq90=-0.06, 95%CI -0.09,-0.04). Conclusions Educational attainment is inversely associated with HbA1c among those with 12 or more years of schooling, with larger point estimates for those in the high-risk tail of the HbA1c distribution.